Electrolyte, lithium ion battery and electric device
Patent Information
- Application Number
- CN202611273668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明的主要目的是提出一种电解液、锂离子电池和用电装置,旨在解决现有技术中LiFSI为电解液锂盐时电池热失控风险较高的问题
[0017] In the technical solution of this invention, a thermally responsive additive with the general chemical formula AZ is added to the electrolyte. The A group of this thermally responsive additive contains a Lewis basic site, and the A group and the Z group are covalently linked. During long-term cycling, various exothermic reactions occur, especially at the interface between the negative electrode and the electrolyte where FSI exists. - The exothermic reduction reaction by lithium metal causes the battery temperature to rise continuously. When the battery temperature is below the dissociation temperature of the Z group, the main framework of the A and Z groups remains stable. At this point, the thermally responsive additive can exist in the electrolyte in a complete molecular form. Due to the large molecular weight of the Z group, it causes steric hindrance to the Lewis basic sites of the A group. Therefore, the A group hardly participates in the formation of the solvation structure, which can ensure FSI. - The SEI film involved in the process is stably formed, resulting in good interfacial stability and electrochemical performance of the battery. When the battery temperature reaches or exceeds the dissociation temperature of the Z group, the Z group dissociates and forms at least two smaller molecular weight groups, one of which contains an A group. This A group has strong Lewis basicity, and its Lewis basic site can rapidly react with Li. + Coordination occurs and Li is competitively occupied. + Solvation of coordination sites in the shell, thereby reducing FSI - The number of anions in the solvated structure suppresses FSI at high temperatures.- The accumulation and reduction decomposition at the interface between the negative electrode and the electrolyte delay thermal runaway; due to the changes of thermal response additives at different temperatures, the battery can operate normally and perform well. When the battery temperature is too high, it can also perform thermal response to delay thermal runaway and ensure battery safety.
Smart Images

Figure CN122931041A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery manufacturing technology, and in particular to an electrolyte, a lithium-ion battery, and an electrical device. Background Technology
[0002] Lithium-ion batteries have been widely used in the new energy field due to their advantages such as high energy density, long cycle life and low self-discharge rate, and have become the core component of electric vehicles, portable electronic devices and energy storage systems.
[0003] Lithium bisfluorosulfonylimide (LiFSI) is a high-performance lithium salt that can improve the conductivity and interfacial stability of the electrolyte. However, LiFSI is prone to violent reactions with lithium metal deposited on the negative electrode side during battery charging and discharging, releasing a large amount of heat and thus increasing the risk of battery thermal runaway. Summary of the Invention
[0004] The main objective of this invention is to provide an electrolyte, a lithium-ion battery, and an electrical device, aiming to solve the problem of high risk of thermal runaway in batteries when LiFSI is used as the electrolyte lithium salt in the prior art.
[0005] To achieve the above objectives, the present invention provides an electrolyte comprising a lithium salt, an organic solvent, and additives: The lithium salt includes lithium bis(fluorosulfonyl)imide; The additive includes a heat-responsive additive with the general chemical formula AZ, wherein the A group includes a group containing a Lewis basic site, the Z group has a molecular weight > 70 Da, and the Z group dissociates at 80~130℃.
[0006] In one embodiment, the Z group includes the LB group, wherein the B group includes a group containing a carbon-carbon double bond and / or an epoxy group, the A group and the B group are connected by an L group, and the L group dissociates at 80~130°C.
[0007] In one embodiment, the A group includes groups with a donor number DN value greater than 10.
[0008] In one embodiment, the A group includes at least one selected from cyano, nitrate, and trifluoroacetate groups.
[0009] In one embodiment, the B group includes a group containing a carbon-carbon double bond, and the group containing a carbon-carbon double bond includes at least one of a vinyl group, an acrylate group, and an allyl group.
[0010] In one embodiment, the vinyl-containing group includes at least one of vinylphenyl and divinylphenyl; and / or, The groups containing acrylate groups include at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, and diacrylate.
[0011] In one embodiment, the L group includes at least one of amide, ester, acetal, imino, dithio, and Diels-Alder adduct groups.
[0012] In one embodiment, the mass of the thermally responsive additive accounts for 0.5% to 10% of the total mass of the electrolyte.
[0013] In one embodiment, the organic solvent includes ether solvents and / or ester solvents.
[0014] In one embodiment, the ether solvent includes at least one selected from 1,3-dioxolane, ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and tetrahydrofuran; and / or, The ester solvent includes at least one of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
[0015] The present invention also provides a lithium-ion battery, wherein the lithium-ion battery includes the aforementioned electrolyte.
[0016] The present invention also provides an electrical device, the electrical device comprising the aforementioned lithium-ion battery.
[0017] In the technical solution of this invention, a thermally responsive additive with the general chemical formula AZ is added to the electrolyte. The A group of this thermally responsive additive contains a Lewis basic site, and the A group and the Z group are covalently linked. During long-term cycling, various exothermic reactions occur, especially at the interface between the negative electrode and the electrolyte where FSI exists. - The exothermic reduction reaction by lithium metal causes the battery temperature to rise continuously. When the battery temperature is below the dissociation temperature of the Z group, the main framework of the A and Z groups remains stable. At this point, the thermally responsive additive can exist in the electrolyte in a complete molecular form. Due to the large molecular weight of the Z group, it causes steric hindrance to the Lewis basic sites of the A group. Therefore, the A group hardly participates in the formation of the solvation structure, which can ensure FSI. - The SEI film involved in the process is stably formed, resulting in good interfacial stability and electrochemical performance of the battery. When the battery temperature reaches or exceeds the dissociation temperature of the Z group, the Z group dissociates and forms at least two smaller molecular weight groups, one of which contains an A group. This A group has strong Lewis basicity, and its Lewis basic site can rapidly react with Li. + Coordination occurs and Li is competitively occupied. + Solvation of coordination sites in the shell, thereby reducing FSI - The number of anions in the solvated structure suppresses FSI at high temperatures.- The accumulation and reduction decomposition at the interface between the negative electrode and the electrolyte delay thermal runaway; due to the changes of thermal response additives at different temperatures, the battery can operate normally and perform well. When the battery temperature is too high, it can also perform thermal response to delay thermal runaway and ensure battery safety. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram of a battery pack according to one embodiment of the present invention; Figure 2 This is a schematic diagram of an energy storage device according to an embodiment of the present invention; Figure 3 This is a schematic diagram of an electrical system according to an embodiment of the present invention.
[0020] Explanation of reference numerals in the attached figures: 1. Battery pack; 11. Housing; 111. Base; 112. Cover; 12. Battery cell; 10. Energy storage device; 101. Box; 100. Power system; 20. Power generation device; 201. Wind turbine assembly; 202. Photovoltaic panel; 30. Wire.
[0021] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Lithium bis(fluorosulfonyl)imide (LiFSI) is a high-performance lithium salt that can improve the conductivity and interfacial stability of electrolytes. In the electrolyte system, LiFSI dissociates to form FSI. - Anions can in Li + The first solvation shell coordinates to form a solvation structure due to FSI - With Li + The interaction is weak, and when the solvated structure migrates to the negative electrode side, Li + It can quickly detach and deposit, while FSI - It can undergo reduction and decomposition before solvent molecules at the interface between the negative electrode and the electrolyte, which facilitates the formation of a LiF-rich solid electrolyte interphase (SEI) film during the first charge and discharge cycle. This SEI film is relatively stable and has low interfacial impedance, thus improving the interfacial stability and electrochemical performance of the battery.
[0024] However, FSI - During long-term charge and discharge cycles, it is prone to violent reactions with lithium metal deposited on the negative electrode side, rapidly releasing a large amount of heat. This results in a faster heat generation rate, which ultimately lowers the battery's thermal runaway trigger temperature (T2), increases the risk of battery thermal runaway, and ultimately increases the probability of battery failure.
[0025] Currently, in order to suppress thermal runaway in batteries using LiFSI as the electrolyte lithium salt, additives that can regulate the solvation structure and reduce free FSI are typically added to the electrolyte. - Concentration of co-solvents (such as acetonitrile) or additives (such as lithium nitrate) can effectively reduce FSI. -The concentration at the interface between the negative electrode and the electrolyte ultimately mitigates thermal runaway and improves battery life. However, these co-solvents or additives can participate in the formation of solvation structures at room temperature, reducing FSI in the solvation structures. - The proportion of [something] deteriorates the SEI film, thereby reducing the interfacial stability and electrochemical performance of the battery under normal operating conditions.
[0026] In view of this, the present invention proposes an electrolyte comprising a lithium salt, an organic solvent, and an additive: the lithium salt comprising lithium bis(fluorosulfonyl)imide; the additive comprising a thermally responsive additive having the general chemical formula AZ, wherein the A group comprises a group containing a Lewis basic site, the Z group has a molecular weight > 70 Da, and the Z group dissociates at 80~130℃.
[0027] In the technical solution of this invention, a thermally responsive additive with the general chemical formula AZ is added to the electrolyte. The A group of this thermally responsive additive contains a Lewis basic site, and the A group and the Z group are covalently linked. During long-term cycling, various exothermic reactions occur, especially at the interface between the negative electrode and the electrolyte where FSI exists. - The exothermic reduction reaction by lithium metal causes the battery temperature to rise continuously. When the battery temperature is below the dissociation temperature of the Z group, the main framework of the A and Z groups remains stable. At this point, the thermally responsive additive can exist in the electrolyte in a complete molecular form. Due to the large molecular weight of the Z group, it causes steric hindrance to the Lewis basic sites of the A group. Therefore, the A group hardly participates in the formation of the solvation structure, which can ensure FSI. - The SEI film involved in the process is stably formed, resulting in good interfacial stability and electrochemical performance of the battery. When the battery temperature reaches or exceeds the dissociation temperature of the Z group, the Z group dissociates and forms at least two smaller molecular weight groups, one of which contains an A group. This A group has strong Lewis basicity, and its Lewis basic site can rapidly react with Li. + Coordination occurs and Li is competitively occupied. + Solvation of coordination sites in the shell, thereby reducing FSI - The number of anions in the solvated structure suppresses FSI at high temperatures. - The accumulation and reduction decomposition at the interface between the negative electrode and the electrolyte delay thermal runaway; due to the changes of thermal response additives at different temperatures, the battery can operate normally and perform well. When the battery temperature is too high, it can also perform thermal response to delay thermal runaway and ensure battery safety.
[0028] In this article, "dissociation" refers to the splitting of the main skeleton of the Z group into two or more smaller molecular groups under thermal action. This splitting can be reversible, for example, after the thermal dissociation of the Diels-Alder adduct, it will regenerate its synthetic precursor, namely a diene group and a dienophile group. This splitting can also be irreversible, for example, after the ester group breaks, it forms a carboxyl residue and a hydroxyl residue. The generated residue may react rapidly with other substances to form a thermodynamically stable new substance that cannot be converted back into the original ester group.
[0029] In this article, "Lewis basic site" refers to an atom or group that can donate lone pairs of electrons (or π electrons) to form a coordinate bond, and therefore can fill Li. + Empty orbitals form coordinate bonds.
[0030] For example, the molecular weight of the Z group can be 71 Da, 80 Da, 100 Da or even higher; the dissociation temperature of the Z group can be 80°C, 90°C, 100°C, 110°C, 120°C or 130°C.
[0031] In some embodiments, the Z group includes the LB group, wherein the B group includes a group containing a carbon-carbon double bond and / or an epoxy group, the A group and the B group are connected by an L group, and the L group dissociates at 80~130°C.
[0032] In the technical solution of this invention, the Z group can be a group obtained by covalently linking the L group and the B group. When the battery temperature is lower than the dissociation temperature of the L group, the responsive additive is stably present in the electrolyte and does not play a role. When the battery temperature reaches or exceeds the dissociation temperature of the L group, the L group dissociates and forms at least two groups with smaller molecular weights, one of which contains an A group. This A group has strong Lewis basicity and can reduce the FSI at the interface between the negative electrode and the electrolyte by participating in the formation of the solvation structure. - Concentration, reduce FSI - The reduction reaction with lithium metal slows down the exothermic rate, thus delaying thermal runaway. One of the groups contains a β group, which, due to its carbon-carbon double bond or epoxy group, can undergo self-polymerization when the battery temperature reaches its self-polymerization temperature. This ultimately forms a polymer at the interface between the negative electrode and the electrolyte. This polymer physically prevents direct contact between the electrolyte and metallic lithium, further reducing FSI. - The reduction reaction with lithium metal reduces the intensity of thermal runaway.
[0033] It should be noted that when the B group is a group containing a carbon-carbon double bond, the carbon-carbon double bond undergoes self-polymerization to form a polymer when the battery temperature reaches the self-polymerization temperature of the carbon-carbon double bond (80~150℃); when the B group contains an epoxy group, the epoxy group undergoes ring-opening polymerization to form a polyether polymer when the battery temperature reaches its ring-opening polymerization temperature (100~150℃).
[0034] For example, the dissociation temperature of the L group can be 80°C, 90°C, 100°C, 110°C, 120°C or 130°C. The dissociation temperature of the L group is preferably 100-120°C, which is between the upper limit of the normal operating temperature of the battery and the critical temperature of thermal runaway, and can provide sufficient reaction time for battery safety protection.
[0035] In some embodiments, the A group includes a group with a donor number DN value greater than 10. That is, the donor number DN value of the Lewis basic site in the A group can be 12, 14, 15 or even higher. Controlling its donor number DN value within the above range can ensure that the Lewis basic site in the A group has a higher coordination ability with lithium ions than FSI. - Strong, it can partially or completely replace the FSI in the solvated structure. - Ultimately reduce FSI - The reaction probability with lithium metal is reduced, the rate of heat generation in the battery is decreased, and thermal runaway is delayed.
[0036] In this article, the donor number (DN) value is used to measure the donation of an electron acceptor Li by a molecule or ion. + The ability or tendency to donate lone pairs of electrons. The higher the DN value, the stronger the electron-donating ability of the solvent or anion, and the stronger the Lewis basicity.
[0037] Preferably, the A group comprises at least one of a cyano group, a nitrate group, and a trifluoroacetate group. That is, the A group can be any one of a cyano group, a nitrate group, and a trifluoroacetate group, or two or more of these groups, all within the scope of this invention. The Lewis basic sites in the aforementioned A group are mainly the nitrogen atom (N) in the cyano group, the oxygen atom in the nitrate group, and the oxygen atom in the trifluoroacetate group. These Lewis basic sites have better coordination ability with lithium ions than FSI. - Therefore, it can rapidly coordinate with lithium ions through L-bond dissociation and bond breaking, occupying coordination sites in the first solvation shell of lithium ions, thereby enabling FSI - Extruded from the lithium-ion solvated shell, significantly reducing FSI at the interface. - The quantity.
[0038] In some embodiments, the B group includes a group containing a carbon-carbon double bond, which includes at least one of a vinyl group, an acrylate group, and an allyl group. When the B group includes a group containing a carbon-carbon double bond, fragments containing the B group are released after the L bond of the thermally responsive additive breaks. When the battery temperature rises to the self-polymerization temperature of the carbon-carbon double bond in the fragment, the carbon-carbon double bond undergoes a self-polymerization reaction to form a polymer. This polymer can act as a physical barrier on the negative electrode side surface, reducing FSI. - The reduction reaction with lithium metal reduces the intensity of thermal runaway.
[0039] Preferably, the vinyl-containing group includes at least one of vinylphenyl and divinylphenyl. The vinyl groups in vinylphenyl and divinylphenyl have carbon-carbon double bonds, which can undergo polymerization (or crosslinking polymerization) at high temperatures of 80-150°C, thereby rapidly forming polystyrene-like polymers (or crosslinked polymers) and ultimately reducing the thermal runaway strength.
[0040] Preferably, the acrylate-containing groups include at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, and diacrylate. The acrylate groups in the hydroxyethyl acrylate, hydroxyethyl methacrylate, and diacrylate groups have carbon-carbon double bonds, which can undergo self-polymerization at high temperatures of 80-150°C to form polyacrylate polymers. More preferably, the diacrylate residue contains two acrylate groups, which can form a dense cross-linked three-dimensional network structure at its self-polymerization temperature, resulting in a polymer with poorer solubility and a stronger physical barrier effect.
[0041] In some embodiments, the L-group includes at least one selected from amide, ester, acetal, imino, dithio, and Diels-Alder adduct groups, wherein the Diels-Alder adduct group is formed by a [4+2] cycloaddition reaction between a diene and a dienophile. The critical temperature for thermal runaway in lithium-ion batteries is typically higher than 200°C, and the upper limit of the normal operating temperature is typically 60°C. The thermal response dissociation temperature or bond breaking temperature of the aforementioned L-group is within the range of 80~130°C, ensuring that the thermal response additive does not dissociate within the normal operating temperature range of the battery (≤60°C) and only functions when the battery abnormally heats up to the thermal runaway trigger temperature.
[0042] The dissociation temperatures of the amide group are 100℃-130℃, the ester group is 90-120℃, the acetal group is 80℃-110℃, the imine group is 90℃-120℃, the disulfide group is 80℃-100℃, and the Diels-Alder adduct is 80℃-130℃. The specific dissociation temperatures of the Diels-Alder adduct can be adjusted by selecting different dienes and diephiles, thereby improving design flexibility.
[0043] In some embodiments, the mass of the thermally responsive additive accounts for 0.5% to 10% of the total mass of the electrolyte. Controlling the mass percentage of the thermally responsive additive within the above range ensures that after the electrolyte temperature rises to the dissociation temperature of the L group, sufficient fragments containing A groups and B groups can be dissociated, ensuring that the A groups can effectively participate in the formation of solvation structures and that the B groups can effectively self-polymerize to form polymers, thereby effectively delaying thermal runaway.
[0044] For example, the mass of the thermally responsive additive is N, and the total mass of the electrolyte is M. The N / M ratio can be 0.5%, 1%, 1.5%, 2.4%, 3.5%, 4.5%, 5.5%, 6.5%, 7.5%, 8.5%, 9.5%, or 10%. When the mass percentage of the thermally responsive additive is less than 0.5%, its effect is limited. When the mass percentage of the thermally responsive additive is greater than 10%, although it can effectively delay thermal runaway, it will increase the DC internal resistance of the battery during normal operation, thereby affecting the electrochemical performance of the battery. More preferably, the N / M ratio is 0.5% to 2%, within which the battery's DCR growth rate is relatively low.
[0045] In some embodiments, the organic solvent includes ether solvents and / or ester solvents. When the battery negative electrode is lithium metal, an ether solvent is preferred, as it exhibits good reduction stability when in contact with the lithium metal negative electrode. Preferably, the ether solvent includes at least one of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), tetraethylene glycol dimethyl ether (TEGDME / G4), and tetrahydrofuran (THF). When the battery negative electrode is graphite, an ester solvent is preferred, as it has good film-forming ability on the graphite surface. Preferably, the ester solvent includes at least one of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate.
[0046] The present invention also provides a lithium-ion battery comprising the aforementioned electrolyte. Therefore, this lithium-ion battery possesses all the beneficial effects of the aforementioned electrolyte, which will not be elaborated further here.
[0047] In some embodiments, the negative electrode of a lithium-ion battery can be a lithium metal sheet or graphite.
[0048] In some embodiments, lithium-ion batteries can be in the form of individual battery cells, or individual battery cells can be assembled into a battery pack, and the number of individual battery cells contained in the battery pack can be one or more.
[0049] Figure 1 This is battery pack 1 as an example. (See reference...) Figure 1 The battery pack 1 may include a housing 11 and a battery cell 12. The housing 11 includes a base 111 and a cover 112. The cover 112 can cover the base 111 and form a closed space to accommodate the battery cell 12.
[0050] The present invention also provides an electrical device comprising the aforementioned lithium-ion battery. Therefore, this electrical device possesses all the beneficial effects of the aforementioned lithium-ion battery, which will not be elaborated further here.
[0051] Figure 2 This is an example of an electrical appliance. (See reference.) Figure 2 The electrical device includes an energy storage device 10, which includes a housing 101 and a plurality of battery packs 1 disposed within the housing 101.
[0052] The aforementioned electrical devices can also be used to build electrical systems.
[0053] Figure 3 An example of an electrical system. (See reference...) Figure 3 The power system includes a power generation device and an energy storage device 20. The power generation device 20 includes a wind turbine assembly 201 and a photovoltaic panel 202. The power generation device 20 and the energy storage device 10 are connected by a wire 30 so that the energy storage device 10 can store the electricity generated by the power generation device 20.
[0054] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0055] Example 1 An electrolyte is prepared by the following steps: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:2:5. Lithium bis(fluorosulfonyl)imide (LiFSI) and a thermal response additive were then added and stirred until homogeneous to obtain an electrolyte. The concentration of LiFSI in the electrolyte was 1M, and the mass of the thermal response additive was 2% of the total mass of the electrolyte. The thermally responsive additive has the chemical formula ALB, as shown in Formula 1. Its structure consists of a sorbitol nitrate group (A group, containing nitrate ester, with a coordination strength DN value of 10~15) linked to an ester group (L group, with a dissociation temperature of 90~120℃) and a hydroxyethyl acrylate group (B group); the total molecular weight of the L group and the B group is 159 Da. C6H9NO7-O-CO-O-CH2-CH2-O-CO-CH=CH2 Formula 1; This thermally responsive additive is prepared through the following steps: Under an inert gas atmosphere, isosorbide 5-mononitrate (1.0 mol) and diphenyl carbonate (1.2 mol) were dissolved in anhydrous tetrahydrofuran, and 4-dimethylaminopyridine (DMAP, 0.05 mol) was added as a catalyst. The reaction was stirred at 60 °C for 6 hours. After the reaction, the solvent was removed by vacuum distillation, and the residue was purified by column chromatography (eluent: petroleum ether / ethyl acetate = 4:1) to obtain intermediate 1 (5-mononitrate isosorbide 5-carbonate). Intermediate 1 (1.0 mol) was dissolved in anhydrous dichloromethane, and hydroxyethyl acrylate (1.1 mol) and 4-dimethylaminopyridine (DMAP, 0.05 mol) were added. The reaction was stirred at 40 °C for 12 hours. After the reaction, the mixture was washed successively with dilute hydrochloric acid, saturated sodium bicarbonate solution, and deionized water. The organic phase was dried over anhydrous sodium sulfate, filtered, and distilled under vacuum to obtain the thermally responsive additive shown in Formula 1.
[0056] Example 2 The difference between Example 2 and Example 1 is that: The thermally responsive additives differ. In Example 2, the thermally responsive additive has the chemical formula ALB, as detailed in Formula 2. Its structure consists of a tris(2-cyanoethyl) acetate group (A group, containing a cyano group and an acetate group, with coordination strength DN values of 14 and 12 for the cyano group and acetate group, respectively) linked to an ester group (L group, with a dissociation temperature of 90~120℃) and a hydroxyethyl acrylate group (B group). The total molecular weight of the L group and the B group is 159 Da. C 14 H 17 N3O2-O-CO-O-CH2-CH2-O-CO-CH=CH2 Formula 2; This thermally responsive additive is prepared through the following steps: Under an inert gas atmosphere, tris(2-cyanoethyl) acetate (1.0 mol) and diphenyl carbonate (1.2 mol) were dissolved in anhydrous tetrahydrofuran, and 4-dimethylaminopyridine (DMAP, 0.05 mol) was added as a catalyst. The reaction was stirred at 60 °C for 6 hours. After the reaction was completed, the solvent was removed by vacuum distillation, and the residue was purified by column chromatography (eluent: petroleum ether / ethyl acetate = 4:1) to give intermediate 1 (tris(2-cyanoethyl) acetate phenyl carbonate). Intermediate 1 (1.0 mol) was dissolved in anhydrous dichloromethane, and hydroxyethyl acrylate (1.1 mol), dicyclohexylcarbodiimide (DCC, 1.1 mol), and 4-dimethylaminopyridine (DMAP, 0.05 mol) were added. The reaction was stirred at 40 °C for 12 hours. After the reaction was completed, the generated dicyclohexylurea (DCU) precipitate was removed by filtration. The filtrate was washed successively with dilute hydrochloric acid, saturated sodium bicarbonate solution and deionized water. The organic phase was dried with anhydrous sodium sulfate, filtered and distilled under reduced pressure to obtain the thermal response additive shown in Formula 2.
[0057] Example 3 The difference between Example 3 and Example 1 is that: The L group is a disulfide bond with a dissociation temperature of 80~100℃; the final total molecular weight of the L and B groups is 210 Da.
[0058] Example 4 The difference between Example 4 and Example 1 is that: The L group is a Diels-Alder adduct with a dissociation temperature of 110~130℃; the final total molecular weight of the L and B groups is 280 Da.
[0059] Example 5 The difference between Example 5 and Example 1 is that: The mass of the thermal response additive is 0.5% of the total mass of the electrolyte.
[0060] Example 6 The difference between Example 6 and Example 1 is that: The mass of the thermal response additive is 10% of the total mass of the electrolyte.
[0061] Example 7 The difference between Example 7 and Example 1 is that: The mass of the thermal response additive is 11% of the total mass of the electrolyte.
[0062] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: No thermal response additives were added, and all other conditions remained the same.
[0063] Performance testing The electrolytes from Examples 1-7 and Comparative Example 1 were used to assemble graphite LFP pouch cells (rated capacity 2.5 Ah), resulting in a total of 8 pouch cell sets. These 8 pouch cell sets were then subjected to the following tests: (1) Charge-discharge cycle test, the specific steps are as follows: Initial capacity calibration: Charge at a constant current of 0.5C (1.25 A) to 3.65 V, then switch to constant voltage charging until the current is ≤0.05C (0.125 A). After standing for 10 min, discharge at a constant current of 0.5C to 2.5 V. Repeat this cycle 3 times and take the stable capacity as the initial capacity. Charge-discharge cycle: The battery after initial capacity correction was charged and discharged at 25℃. Specifically, it was charged at a constant current of 1C (2.5 A) to 3.65 V, then charged at a constant voltage until the current was ≤0.05C (0.125 A). After resting for 10 min, it was discharged at a constant current of 1C (2.5 A) to 2.5 V. After resting for 10 min, the above charge-discharge procedure was repeated until the charge-discharge cycle was 500 times. Capacity retention rate = (500th discharge capacity / initial discharge capacity) × 100%; (2) DC internal resistance (DCR) test, the specific steps are as follows: adjust the battery to 50% SOC, apply a 1C current to the battery for 10s, record the voltage value before and after the pulse, calculate the resistance value according to Ohm's law, take the group without additives as the base group, and obtain the DCR deterioration rate by comparing the resistance difference between the example and the base group. (3) Adiabatic accelerated calorimetry (ARC) test: After the battery is fully charged, it is placed in the ARC chamber and tested in the Heat-Wait-Seek (HWS) mode. The thermal runaway trigger temperature (T2) and the thermal runaway maximum temperature (T3) are recorded. T2 refers to the temperature when the battery temperature rise rate (dT / dt) reaches 1℃ / s, and T3 refers to the peak temperature when the internal chain exothermic reaction of the battery reaches the most intense state during the thermal runaway process. The results are shown in Table 1.
[0064] Table 1. Electrochemical performance characterization of the pouch cells corresponding to Examples 1-7 and Comparative Example 1.
[0065] As shown in Table 1: Compared with Comparative Example 1, the capacity retention rates of the pouch cells corresponding to Examples 1-7 after 500 cycles were not significantly different from those of Comparative Example 1. This indicates that the thermally responsive additive provided by the present invention exists in its complete molecular form at room temperature and does not interfere with FSI. -The solvation coordination by FSI - The dominant LiF-rich high-quality SEI film formed normally, and the battery maintained its cycle performance at room temperature. In Examples 1 and 5, the electrolyte addition amounts were 2% and 0.5%, respectively, resulting in lower DCR growth rates. However, the T2 values of Examples 1-8 were significantly higher than those of Comparative Example 1. This indicates that when the battery temperature reaches or exceeds the L-bond dissociation temperature, the thermally responsive additive breaks down at the L-bond, releasing at least a small molecule fragment containing an A group. This allows the Lewis basic sites in the A group to coordinate with lithium ions to form a solvated structure, reducing the FSI in all solvated structures. - The ratio effectively reduces the FSI at the electrolyte and negative electrode interface. - The quantity suppressed the effect of lithium metal on FSI in the negative electrode. - The reduction decomposition reaction, as its rate decreases, leads to a decrease in the heat generation rate. The temperature required for the battery to reach the critical value for heat dissipation (i.e., T2) is higher, ultimately delaying the triggering of thermal runaway. Simultaneously, FSI... - The suppression of the negative electrode reduction reaction also reduces the formation of corresponding byproducts, thereby blocking or weakening the intensity of the subsequent strong exothermic chain reaction, resulting in a decrease in the total heat release of the battery and a corresponding decrease in T3. It should be noted that the impact of Example 5 on thermal runaway is less than that of the other examples. This is because the other examples simultaneously release fragments containing A and B groups. The B group contains a self-polymerizing functional group, which can therefore polymerize in situ at high temperatures to form a polymer protective layer, thereby effectively blocking the contact between the electrolyte and the negative electrode on the negative electrode side, further suppressing the rate of FSI. - The reduction reaction at the negative electrode ultimately leads to better improvements in T2 and T3.
[0066] A comparison of Examples 1, 3, and 4 shows that the earlier the L fracture temperature occurs, the better the thermal runaway of the battery cell can be suppressed. A comparison of Examples 1, 5, 6, and 7 shows that increasing the content of thermal response additives worsens the cell's thermal conductivity (DCR), but all are within acceptable limits. The improvement in the cell's thermal safety performance becomes more pronounced with increasing thermal response additive content.
[0067] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.
Claims
1. An electrolyte, characterized in that, The electrolyte includes lithium salt, organic solvent, and additives: The lithium salt includes lithium bis(fluorosulfonyl)imide; The additive includes a heat-responsive additive with the general chemical formula AZ, wherein the A group includes a group containing a Lewis basic site, the Z group has a molecular weight > 70 Da, and the Z group dissociates at 80~130℃.
2. The electrolyte as described in claim 1, characterized in that, The Z group includes the LB group, wherein the B group includes a group containing a carbon-carbon double bond and / or an epoxy group, the A group and the B group are connected by an L group, and the L group dissociates at 80~130℃.
3. The electrolyte as described in claim 2, characterized in that, The A group includes groups with a donor number DN value greater than 10.
4. The electrolyte as described in claim 3, characterized in that, The A group includes at least one of cyano, nitrate, and trifluoroacetate groups.
5. The electrolyte as described in claim 2, characterized in that, The B group includes groups containing carbon-carbon double bonds, and the groups containing carbon-carbon double bonds include at least one of groups containing vinyl groups, groups containing acrylate groups, and groups containing allyl groups.
6. The electrolyte as described in claim 5, characterized in that, The vinyl group includes at least one of vinylphenyl and divinylphenyl; and / or, The groups containing acrylate groups include at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, and diacrylate.
7. The electrolyte as described in claim 2, characterized in that, The L group includes at least one of amide, ester, acetal, imino, dithio, and Diels-Alder adduct groups.
8. The electrolyte as described in claim 1, characterized in that, The mass of the thermally responsive additive accounts for 0.5% to 10% of the total mass of the electrolyte.
9. The electrolyte as described in claim 1, characterized in that, The organic solvents include ether solvents and / or ester solvents.
10. The electrolyte as described in claim 9, characterized in that, The ether solvent includes at least one selected from 1,3-dioxolane, ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and tetrahydrofuran; and / or, The ester solvent includes at least one of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
11. A lithium-ion battery, characterized in that, The lithium-ion battery includes the electrolyte as described in any one of claims 1 to 10.
12. An electrical appliance, characterized in that, The electrical device includes the lithium-ion battery as described in claim 11.